Nostra Aetate and the Future of Jewish-Christian Relations - Brettler, Marc Zvi (Studies in Christian-Jewish Relations, 2025)
The promulgation of Nostra Aetate was most significant for opening the door to Catholic-Jewish dialogue. It was progressive in some ways, especially in denying the claim of deicide, but left much room for warmer attitudes toward Jews and Judaism; this was rectified in later Vatican documents. Eventually, Jewish statements, such as Dabru Emet (2000), responded positively to these Catholic overtures. Yet, further progress is needed, as the Christian community must deal honestly with supersessionism, and the Jewish community with chosen-ness.